Pollen exposure is associated with risk of respiratory symptoms during the first year of life. Issue 12 (28th March 2022) - Gisler, Amanda; Eeftens, Marloes; de Hoogh, Kees; Vienneau, Danielle; Salem, Yasmin; Yammine, Sophie; Jakob, Julian; Gorlanova, Olga; Decrue, Fabienne; Gehrig, Regula; Frey, Urs; Latzin, Philipp; et al.
Abstract: Background: Pollen exposure is associated with respiratory symptoms in children and adults. However, the association of pollen exposure with respiratory symptoms during infancy, a particularly vulnerable period, remains unclear. We examined whether pollen exposure is associated with respiratory symptoms in infants and whether maternal atopy, infant's sex or air pollution modifies this association. Methods: We investigated 14, 874 observations from 401 healthy infants of a prospective birth cohort. The association between pollen exposure and respiratory symptoms, assessed in weekly telephone interviews, was evaluated using generalized additive mixed models (GAMMs). Effect modification by maternal atopy, infant's sex, and air pollution (NO2, PM2.5 ) was assessed with interaction terms. Results: Per infant, 37 ± 2 (mean ± SD) respiratory symptom scores were assessed during the analysis period (January through September). Pollen exposure was associated with increased respiratory symptoms during the daytime (RR [95% CI] per 10% pollen/m 3 : combined 1.006 [1.002, 1.009]; tree 1.005 [1.002, 1.008]; grass 1.009 [1.000, 1.23]) and nighttime (combined 1.003 [0.999, 1.007]; tree 1.003 [0.999, 1.007]; grass 1.014 [1.004, 1.024]). While there was no effect modification by maternal atopy and infant's sex, a complex crossover interaction between combined pollen and PM2.5 was found ( p ‐value 0.003). Conclusion: Even as early as during the first year of life, pollen exposure was associated with an increased risk of respiratory symptoms, independent of maternal atopy and infant's sex. Because infancy is a particularly vulnerable period for lung development, the identified adverse effect of pollen exposure may be relevant for the evolvement of chronic childhood asthma. Abstract : This longitudinal study included 401 healthy infants from the Basel‐Bern Infant Lung Development (BILD) cohort. The association between pollen exposure and weekly telephone‐assessed respiratory symptoms was evaluated. Increased exposure to tree and grass pollen, both combined and separately, was associated with an increased risk of respiratory symptoms during the first year of life. There was no effect modification by maternal atopy and infant's sex; however, we found a complex interaction between combined pollen and PM2.5 . Abbreviations: PM2.5, particulate matter with an aerodynamic diameter ≤ 2.5 μm